Causes of Pneumonia Epizootics among Bighorn Sheep, Western United States, 2008–2010 - Besser, Thomas E.; Highland, Margaret; Baker, Katherine; Cassirer, E. Frances; Anderson, Neil J.; Ramsey, Jennifer M.; Mansfield, Kristin; Bruning, Darren L.; Wolff, Peregrine; Smith, Joshua B.; Jenks, Jonathan A. (Emerging infectious diseases, 2012)
Epizootic pneumonia of bighorn sheep is a devastating disease of uncertain etiology. To help clarify the etiology, we used culture and culture-independent methods to compare the prevalence of the bacterial respiratory pathogens Mannheimia haemolytica, Bibersteinia trehalosi, Pasteurella multocida, and Mycoplasma ovipneumoniae in lung tissue from 44 bighorn sheep from herds affected by 8 outbreaks in the western United States. M. ovipneumoniae, the only agent detected at significantly higher prevalence in animals from outbreaks (95%) than in animals from unaffected healthy populations (0%), was the most consistently detected agent and the only agent that exhibited single strain types within each outbreak. The other respiratory pathogens were frequently but inconsistently detected, as were several obligate anaerobic bacterial species, all of which might represent secondary or opportunistic infections that could contribute to disease severity. These data provide evidence that M. ovipneumoniae plays a primary role in the etiology of epizootic pneumonia of bighorn sheep.